2014
DOI: 10.3109/02652048.2013.863397
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of liquid and solid substances by reactive polymers

Abstract: This study is devoted to the development of techniques for the formation of polymeric microcapsules (MC) with either liquid or solid core and with the polymer shell containing diverse functional groups on the basis of new reactive functional copolymers (FC). Two approaches to the formation of MC containing FC shell that included the stages of "oil-in-water" or "water-in-oil" dispersion preparation followed by slow extraction of solvents from dispersed phase by dispersive media were examined. FC with the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Traditionally, TEMs are prepared from fossil-based monomers such as acrylonitrile (AN), methacrylonitrile (MAN), various (meth)acrylates, maleimides, acrylamides, vinylidene chloride, and styrene. 30 Considering the increasing need to replace fossil-based plastics, there is, surprisingly, limited work on TEMs synthesized from bio-based monomers. 10,24,26 TEMs can be prepared using different heterogeneous polymerization methods; however, the most common method used industrially is free-radical suspension polymerization where a blowing agent, typically a branched hydrocarbon, is encapsulated inside the obtained polymer microspheres.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, TEMs are prepared from fossil-based monomers such as acrylonitrile (AN), methacrylonitrile (MAN), various (meth)acrylates, maleimides, acrylamides, vinylidene chloride, and styrene. 30 Considering the increasing need to replace fossil-based plastics, there is, surprisingly, limited work on TEMs synthesized from bio-based monomers. 10,24,26 TEMs can be prepared using different heterogeneous polymerization methods; however, the most common method used industrially is free-radical suspension polymerization where a blowing agent, typically a branched hydrocarbon, is encapsulated inside the obtained polymer microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies where polymerization parameters including the effect of crosslinking, 1,12–19 structure, 20 surface modification, 21–25 and applications 2,26–29 have been investigated. Traditionally, TEMs are prepared from fossil‐based monomers such as acrylonitrile (AN), methacrylonitrile (MAN), various (meth)acrylates, maleimides, acrylamides, vinylidene chloride, and styrene 30 . Considering the increasing need to replace fossil‐based plastics, there is, surprisingly, limited work on TEMs synthesized from bio‐based monomers 10,24,26 …”
Section: Introductionmentioning
confidence: 99%
“…For the past 30 years, our research group carried out studies in the field of synthesis of reactive surface-active peroxide-containing copolymers and the creation of micro, nano-objects, and various polymer composites based on them with adjustable physical and mechanical properties. [30][31][32][33] Such reactive copolymers are engaged in cross-linking polymer materials through chain transfer reactions initiated by peroxide fragments present in their structure or as a result of reactions of functional groups (anhydride, carboxyl, amino groups) with functional fragments of biocompatible polymers. [31][32][33] It should be noted that peroxide-containing copolymers based on 5-(tertbutyl peroxy)-5-methylhex-1-en-3-yne, similar to those used in the present work, were shown to be biocompatible and non-toxic when studied as nanocarriers for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…This task is not always easy resolvable. The links of peroxide monomer are highly hydrophobic, its copolymers with polar hydrophilic monomers (like acrylic or methacrylic acids, maleic anhydride 23,30,31 ) are well soluble in polar organic solvents, but they are not soluble in water, just only in alkali aqueous solutions at pH >7.0. At the same time, many of the natural and synthetic biocompatible polymers are poorly soluble in organic solvents, rather than in water media, while alkali aqueous solutions are not always appropriate because they can cause the hydrolysis of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The modification of their surface with a proper modifier can enhance the compatibility of NP with a polymer matrix. Our previous investigations have shown that reactive (including peroxide‐containing) copolymers are the promising agents for the modification and activation of colloidal particles of different nature (both organic and inorganic) 16,21–23 . Such modification of colloid surface provides an opportunity for the formation of filled composite materials of various nature with a three‐dimensional network structure and improved physico‐mechanical properties due to non‐specific radical reactions such as chain transfer, and chain break, grafted polymerization initiated by peroxide groups immobilized on the colloidal particle surface.…”
Section: Introductionmentioning
confidence: 99%